Tariff Evasion and Customs Corruption : Does Pre-Shipment Inspection Help? - Anson, Jose (World Bank, Washington, DC, 2014)
The authors provide a new approach to the evaluation of pre-shipment inspection (PSI) programs as ways of improving tariff-revenue collection and reducing fraud when customs administrations are corrupt. They build a model highlighting the contribution of surveillance firms to the generation of information and describing how incentives for fraud and collusive behavior between importers and customs are affected by the introduction of PSI. The authors show theoretically that the introduction of PSI has an ambiguous effect on the level of customs fraud. Empirically, the econometric results suggest that PSI reduced fraud in the Philippines, it increased it in Argentina, and did not have significant impact in Indonesia.